The Role of On-site Coulumb Interaction on Electronic Structure of FeO: Irwan Ramli, Nirmala Arfa, Rahma Hi Manrulu, Fitri Jusmi - Irwan Ramli Irwan Ramli; Nirmala Arfa Nirmala Arfa; Rahma Hi Manrulu Rahma Hi Manrulu; Fitri Jusmi Fitri Jusmi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2022)
We report our density functional theory (DFT) calculation on FeO in order to describe its electronic properties. FeO exhibits an antiferromagnetic at the ground state with cubic structure and Neel temperature TN = 198 K. The DFT calculation is as powerful tool to describe electronic properties but known to be failed to describe the electronic properties of system with strong on-site Coulomb interaction such as FeO. Here, we introduce the Hubbard correction, U, in order to take into account the on-site Coulomb interaction of d-electron at Fe ion. Hybridization of 3d-electron of Fe and 2p-electron of O splits the energy level to become upper Hubbard band (UHB) and low Hubbard band (LHB). Based on the DFT+U calculation, the band structure of FeO shows an insulator feature with the band gap of 1.65 eV, and its density of state (DOS) implies that this gap arises from splitting 3d-electron of Fe.